A comparison of ionosonde measured foF2 and IRI-2016 predictions over China. Issue 6 (15th March 2019) - Liu, Zhendi; Fang, Hanxian; Weng, Libin; Wang, Sicheng; Niu, Jun; Meng, Xing
Abstract: A comparison of the ionospheric F-region critical frequency (foF2) between ionosonde measurements and IRI-2016 predictions is studied over China during the period from January 2008 to October 2016. Four stations are selected, and the latitude coverage starts at 49.4°N and ends at 23.2°N with a sequential latitude interval of about 10°, the corresponding geomagnetic latitudes are from 39.5°N to 13.2°N. The results show that the variability of the observed foF2 versus latitudes, seasons, local time and levels of solar activity could be well reproduced by IRI-2016. However, the daily lowest value of foF2 from the IRI-2016 prediction occurs earlier than that from the ionosonde. Around the sunrise, the IRI-2016 prediction shows a very sharp rise and grows much faster than the observed foF2 in every month. The foF2 difference between the two options (URSI and CCIR) in IRI-2016 increases as the F10.7 index decreases. During 2008–2009, the annual average deviations of URSI and CCIR range from −5% to −10% and from 5% to −5%, respectively. Generally, the CCIR performs better than URSI during postsunset under low solar activity or in Equatorial Ionization Anomaly (EIA) region over China, while it shows no large difference in performance with URSI in other locations or for other time.